دور ممارسات الذكاء الاصطناعي في تحسين التميز المؤسسي في الميدان الرياضي - زيتوني ، نبيل; Supervisor : خضار ، خالد (Mohamed Boudiaf University of M'Sila, 2025)
الملخص : بالعربية:تهدف دراستنا هذه إلى تسليط الضوء على دور ممارسات الذكاء الاصطناعي في تحسين التميز المؤسسي في الميدان الرياضي، وذلك من خلال استعراض ووصف وتحليل لبعض نتائج الدراسات التي تناولت نماذج الذكاء الاصطناعي في المؤسسات الرياضية. وأسفرت النتائج على أن ممارسات الذكاء الاصطناعي تؤدي إلى تحسين التميز المؤسسي في المؤسسات الرياضية، وذلك من خلال تحسين أداء العاملين في المؤسسة الرياضية كذلك تحسين عملية اتخاذ القرار في إدارتها وهذا بالطبع يساهم بشكل كبير في النجاح في تنظيم التظاهرات الرياضية. عنوان الدراسة : دور ممارسات الذكاء الاصطناعي في تحقيق التميز المؤسسي في الميدان الرياضي أهداف الدراسة :. - الوصول إلى معرفة دور ممارسات الذكاء الاصطناعي في تحسين التميز المؤسسي في الميدان الرياضي من خلال مجالات رياضية. - إبراز أهم تطبيقات الذكاء الاصطناعي. - إبراز مدى مساهمة ممارسات تقنيات الذكاء الاصطناعي في تحسين أداء العاملين. - تهدف الدراسة الى تزويد الادارة بمجموعة من التوصيات والاقتراحات في ضوء نتائج الدراسة والتي تمكنها من علاج عقبات التميز. التساؤل العام الدراسة : ما هو دور ممارسات الذكاء الاصطناعي في تحسين التميز المؤسسي في الميدان الرياضي؟ التساؤلات الجزئية : 1. إلى أي مدى تسهم ممارسات الذكاء الاصطناعي في تحسين أداء العاملين في الميدان الرياضي؟ 2. كيف يمكن للذكاء الاصطناعي تحسين عملية اتخاذ القرارات في المؤسسات الرياضية؟ الفرضية العامة للدراسة : - تسهم ممارسات الذكاء الاصطناعي بفاعلية في تحقيق التميز المؤسسي في الميدان الرياضي. الفرضيات الجزئية أ- تساهم تقنيات الذكاء الاصطناعي في تحسين أداء العاملين بدرجة كبيرة. ب- مدى فعالية تقنيات الذكاء الاصطناعي في عملية اتخاذ القرار بالمؤسسة. المنهج المتبع في الدراسة : اعتمد الباحث على المنهج الوصفي، الذي يعتبر طريقة من طرق تحليل والتفسير بشكل علمي منظم بغية الوصول إلى أهداف محددة لظاهرة ما، كما أنه يعتمد على دراسة الظاهرة كما توجد في الواقع ويهتم بوصفها بشكل دقيق ويعبر عنها كمياً او كيفيا. الأدوات المستخدمة في الدراسة برنامج SPSS 25 الكلمات المفتاحية بالعربية الكلمات المفتاحية: الذكاء الاصطناعي، المؤسسات الرياضية، التميز المؤسسي. بالإنجليزية Keywords: Artificial Intelligence, Sports Organizations, Institutional Excellence جاء هذا البحث في فصول . الفصل الأول: الإطار العام للدراسة وتناول الفصل الثاني: ماهية الذكاء الاصطناعي أما الفصل الثالث: المؤسسات الرياضية الفصل الرابع: الإجراءات المنهجية للدراسة من أهم النتائج التي توصل إليها الباحث من خلال ما تناولناه في هذه الدراسة بجانبيها النظري والتطبيقي فيما يخص دور ممارسات الذكاء الاصطناعي في تحسين التميز المؤسسي في الميدان الرياضي، وبعد قيامنا بمعالجة البيانات والمعلومات توصلت الدراسة إلى النتائج:  درجة ممارسات الذكاء الاصطناعي في تحسين التميز المؤسسي في الميدان الرياضي (مديرية الشباب والرياضة لولاية برج بوعريريج) مرتفعة.  مستوى مساهمة الذكاء الاصطناعي في تحسين أداء العاملين مرتفع في المؤسسة الرياضية (مديرية الشباب والرياضة لولاية برج بوعريريج)  درجة فعالية الذكاء الاصطناعي في عملية اتخاذ القرار في المؤسسة الرياضية مرتفع. أهم التوصيات • زيادة الاهتمام بتطبيقات الذكاء الاصطناعي في المجال الرياضي من خلال توفير الأدوات والوسائل والحوافز التي يمكن أن تساهم في تطوير أداء المؤسسات الرياضية. • تنظيم دورات تدريبية حول كيفية استخدام تطبيقات الذكاء الاصطناعي. • تنظيم أيام دراسية وندوات حول أهمية استخدام تطبيقات الذكاء الاصطناعي في المؤسسة الرياضية. • فتح معاهد وكليات خاصة بالذكاء الاصطناعي متخصصة في الميدان الرياضي لكي لا نبقى دولاً مستهلكة ومجبورة على شراء الآلات والمعدات بأغلى الأثمان في الوقت الذي تكون فيها الدول الأخرى قد قطعت أشواطا في تطوير تكنولوجيتها فيما يرتبط بالذكاء الاصطناعي. • ضرورة مواكبة ومسايرة المؤسسات الرياضية للتطورات الحاصلة في مجال الذكاء الاصطناعي الحديث والاطلاع على كل ما هو جديد ومتطور من مختلف الوسائل الإعلامية والاتصالية ومحاولة تحديثها باعتبارها أصبحت تشكل تحديا كبيرا للمؤسسات الرياضية المعاصرة . • إجراء المزيد من الندوات واللقاءات اللازمة لإزالة مخاوف العمال من الغموض حول تطبيقات الذكاء الاصطناعي. • تشجيع الباحثين على تناول موضوع تطبيقات الذكاء الاصطناعي من جوانب أخرى. Searchlight in English Faculty Institute of Sciences and Sports and Technical and Physical Activities Department: Order No: No. d 'registration : 20033099597 Searcher : ZITOUNI NABIL Publicly supported on Title of the thesis (dissertation): The role of artificial intelligence practices in improving institutional performance in the sports field Language of the thesis: ARABIC Model of the thesis: Master Country: REPUBLIC OF ALGERIA-M'SILA University: University of M'sila Surname and first name of the supervisor : KHADAR KHALED Grade: Dr Lecturer Number of pages: 80 Option: Sports facilities management and human resources Summary: This study aims to shed light on the role of artificial intelligence practices in improving institutional excellence in the sports field. This is achieved by reviewing, describing, and analyzing some of the results of studies that addressed artificial intelligence models in sports organizations. The results revealed that artificial intelligence practices lead to improved institutional excellence in sports organizations, by enhancing the performance of employees within the sports organization and improving the decision-making process within its management. This, of course, contributes significantly to the success of organizing sporting events. Title of the study: The role of artificial intelligence practices in improving institutional performance in the sports field The purpose of the study • Increase interest in artificial intelligence applications in sports by providing tools, means, and incentives that can contribute to improving the performance of sports institutions. • Organize training courses on how to use artificial intelligence applications. • Organize study days and seminars on the importance of using artificial intelligence applications in sports institutions. • Establish artificial intelligence institutes and colleges specializing in sports to prevent us from remaining consumer countries forced to purchase expensive machinery and equipment at a time when other countries have made significant strides in developing their artificial intelligence technologies. • Sports institutions must keep pace with developments in the field of modern artificial intelligence, and be informed of all new and advanced media and communication tools and endeavor to modernize them, as they have become a major challenge for contemporary sports institutions. • Hold more seminars and meetings to alleviate workers' fears about the ambiguity surrounding artificial intelligence applications. • Encourage researchers to address the topic of artificial intelligence applications from other perspectives. Problem: What is the role of artificial intelligence practices in improving institutional excellence in the sports field? Hypotheses: General Hypothesis of the Study: - Artificial intelligence practices contribute effectively to achieving organizational excellence in the sports field. Sub-Hypotheses: A- Artificial intelligence technologies contribute significantly to improving employee performance. B- The extent of the effectiveness of artificial intelligence technologies in the decision-making process within the organization. Keywords: Artificial Intelligence, Sports Organizations, Institutional Excellence - The most important results achieved are: Through the theoretical and applied aspects of this study, we examined the role of artificial intelligence practices in improving institutional excellence in the sports field. After processing the data and information, the study reached the following conclusions: • The degree of artificial intelligence practices in improving institutional excellence in the sports field (the Directorate of Youth and Sports of the state of Bordj Bou Arreridj) is high. • The level of artificial intelligence's contribution to improving employee performance is high in the sports institution (the Directorate of Youth and Sports of the state of Bordj Bou Arreridj). • The degree of effectiveness of artificial intelligence in the decision-making process in the sports institution is high.
Keywords: الذكاء الاصطناعي; المؤسسات الرياضية; التميز المؤسسي